Dayn Dalam Perspektif Al-Qur’an: Analisis Terhadap Kitab Tafsir Al-Munir Karya Wahbah Zuhaili - Nurmaiya Rahmi; Syafruddin Syafruddin; Efrinaldi Efrinaldi; Edriagus Saputra (Hikmah, 2022)
This study aims to reveal the use of the concept of dayn in the Qur'an which is used by institutions today. This research uses a qualitative method with a library research model on the meaning of the dayn perspective of the Qur'an in the book Tafsir Al-Munir by Wahabh Zuhaili. This study uses the maudhu'i interpretation method by referring to the steps formulated by Dr. Zulheldi. M.Ag. The results of this study can be concluded that dayn in the Qur'an according to Wahbah az-Zuhaili in his commentary book on surah al-Baqarah 282, namely assets that are still in the status of not being handed over in its entirety to the rightful party. Both in the form of buying and selling, greetings, and accounts payable. Where the transaction is not carried out in cash. Then the contextualization of dayn in the greeting contract in the contemporary era among its forms, namely: the greeting contract in online applications. While the contextualization of dayn in the form of lending and borrowing in the contemporary era, namely borrowing and borrowing based on debt and credit technology is done online, borrowing money from moneylenders, borrowing money at banks, both Islamic banks and conventional banks, according to Wahbah az-Zuhaili, some are not. according to the guidance of the Qur'an.